Everybody Loves Trees : Policing American Cities Through Street Trees - Braverman, Irus (2008)
Recently, municipalities have been investing large sums of money as well as much bureaucratic and professional effort into making their cities not only a more treefull place, but also a place that surveys, measures, regulates, and manages its trees. This article explores the transformation of the utilitarian discourse on trees, which focuses on the benefits of trees and greenery, into a normative discourse whereby trees are not only considered good but are also represented as if they are or should be loved by everybody. This transformation is not only the result of top-down governmental policies. It is also a consequence of longstanding romantic views of nature in the city - especially in the American city - facilitated by environmental organizations, local communities, and individual activists. Importantly, the attribution of morality to tree practices masks the clandestine project of governing the urban population and the control of city crime in particular